The relationship between frailty and serum alpha klotho levels in geriatric patients. (November 2020) - Polat, Yasemin; Yalcin, Ahmet; Yazihan, Nuray; Bahsi, Remzi; Mut Surmeli, Deniz; Akdas, Sevginur; Aras, Sevgi; Varli, Murat
Highlights: Klotho gene is known as an anti-aging gene with many functions. Alpha klotho protein can be tested in serum and the test is non-invasive. This serum biomarker is a good indicator of inflammation. Serum alpha klotho protein level may be associated with frailty among older adults. This serum biomarker is a good indicator of diagnosis of cognitive dysfunction. Abstract: Background: Frailty is a medical syndrome resulting in loss of endurance, strength and physiological function. There is insufficient data to understand the process of frailty formation at the gene level, however one of the product of Klotho gene known as an anti-aging gene with many functions that prolong lifespan is alpha klotho protein. We aimed to investigate the relationship between frailty and the serum alpha klotho protein levels. Methods: In this cross-sectional analysis, there were 89 patients aged 65 years old and older, 45 of whom were frail and 44 of whom were not frail, were included in the study. Within the scope of the study, a sociodemographic and clinical information form, the Turkish version of the FRAIL scale and a comprehensive geriatric assessment were evaluated. In addition to routine laboratory tests, plasma alpha klotho protein levels were measured. Results: The mean alpha klotho protein levels of the patients were 0.76 ± 1.01 ng/ml in the control group and 0.54 ± 0.61 ng/ml in the frail group, however, there was no statistically significant difference between the two groups (p = 0.286). C-reactive protein (CRP) levels were significantly higher and hemoglobin (Hb) levels were significantly lower in the frail patients compared to the control group (p < 0.05). It was observed that alpha klotho protein level was inversly correlated with increased CRP levels but association was weak (p = 0.022, R: −0.245). Hb levels (p = 0.018, R: 0.250) was weakly correlated with alpha klotho protein level. Conclusion: No significant relationship was found between frailty and alpha klotho protein levels in the geriatric patients. Further comprehensive studies are needed to explore this subject.